The texture of the divine: imagination in medieval Islamic and Jewish thought - Hughes, Aaron W. (Indiana University Press, 2004)
The Texture of the Divine explores the central role of the imagination in the shared symbolic worlds of medieval Islam and Judaism. Aaron W. Hughes looks closely at three interrelated texts known as the Hayy ibn Yaqzan cycle (dating roughly from 1000--1200 CE) to reveal the interconnections not only between Muslims and Jews, but also between philosophy, mysticism, and literature. Each of the texts is an initiatory tale, recounting a journey through the ascending layers of the universe. These narratives cu